Rapid hydrothermal synthesis route for nanocrystalline SrZrO3 using reactive precursors - Athawale, Anjali A.; Chandwadkar, Asha J.; Karandikar, Prashant R.; Bapat, Malini S. (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
Synthesis of nanocrystalline, orthorhombic (space group Pnma) SrZrO3 was achieved using appropriate molar proportions of nitrate salts of strontium and zirconium as precursors. Formation of SrZrO3 (SZ) was facilitated hydrothermally in time period as less as half-an-hour, in aqueous medium with alkaline pH as confirmed by XRD. Sample characterization was performed by FT-IR spectroscopy; powder XRD, SEM, TEM and DSC. The results have been explained by proposing a suitable reaction mechanism based on the step-wise analysis of the reaction intermediates using FT-IR as well as XRD. A double cation hydroxide composite formation is anticipated that under hydrothermal conditions results in the formation of SrZrO3. Morphology of the samples was determined with the help of SEM and TEM. The particle size distribution as seen from the TEM micrograph lies in the range of 15-25 nm. Heats of reaction for different decomposition steps were obtained by DSC. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Crystallization; diffraction; Electron microscopy; infrared spectroscopy

Radiation assisted synthesis of nanosized barium zirconate - Athawale, Anjali A.; Chandwadkar, Asha J.; Karandikar, Prashant R.; Pasricha, R.; Bapat, Malini S. (Radiation Physics and Chemistry, 2006)
This paper reports the synthesis of refractory barium zirconate using solid-state reactive precursors subjected to gamma-radiations of a Co-60 source. Influence of varying doses on the formation of cubic phase of BaZrO3 has been investigated with the stepwise analysis of the intermediate products by means of FT-IR, XRD and TGA techniques. TEM depicts the nanospherical nature of the BaZrO3 particles. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; gamma-radiation; Nanoparticles; perovskite; refractory; XRD